2016
DOI: 10.1007/s10342-016-0994-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between landscape configuration and plant species richness in forests is dependent on habitat preferences of species

Abstract: To assess the effects of landscape configuration on local plant species richness, we tested whether local species richness of forest understory plants is affected by the total forest area and forest edge length in the adjacent landscape. We also tested whether the landscape effect on species richness is different for forest and edge species. We estimated species richness from 113 forest sites in four regions in Northern Europe. At each site, we studied two plots, one at the edge and one in the core of the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
6
0
1
Order By: Relevance
“…Besides land-use composition, land-use configuration can in some cases represent a good proxy for those species requiring corridors and landscape borders to survive (e.g., Neilan et al, 2019;Vinter et al, 2016). Accordingly, the heterogeneity of land-use or of satellite reflectance data has been widely assessed in the past, using various algorithms and metrics such as multivariate statistical analysis (Feilhauer and Schmidtlein, 2009), the spectral species concept (Féret and Asner, 2014), self-organizing feature maps (Foody, 1999), multidimensional distance metrics (Rocchini et al, 2016), and Rao's Q diversity (Rocchini et al, 2017).…”
Section: Direct Anthropogenic Pressurementioning
confidence: 99%
“…Besides land-use composition, land-use configuration can in some cases represent a good proxy for those species requiring corridors and landscape borders to survive (e.g., Neilan et al, 2019;Vinter et al, 2016). Accordingly, the heterogeneity of land-use or of satellite reflectance data has been widely assessed in the past, using various algorithms and metrics such as multivariate statistical analysis (Feilhauer and Schmidtlein, 2009), the spectral species concept (Féret and Asner, 2014), self-organizing feature maps (Foody, 1999), multidimensional distance metrics (Rocchini et al, 2016), and Rao's Q diversity (Rocchini et al, 2017).…”
Section: Direct Anthropogenic Pressurementioning
confidence: 99%
“…In Central European forests, the recent species richness still reflects episodes that occurred in the previous century, such as forest patch shrinkage or loss of connectivity between forest patches [23,24]. Therefore, historical knowledge regarding forest distribution is necessary for understanding the recent species richness distribution, as well as for conservation management planning [11,25].…”
Section: Introductionmentioning
confidence: 99%
“…Conservation planners need to preserve resilient habitat networks, and this requires identification of habitat patches and corridors that are crucial for maintaining or establishing the connectivity of fragmented populations [25][26][27]. Changes in the landscape structure also affect the mutualistic relationships between plants and pollinating insects, which may, among others, limit the availability of pollen and consequently decrease the viability of plant populations [28].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, edge effects may be positive instead of negative. In our study system, Vinter, Dinnétz, Danzer, and Lehtilä () observed that species richness was higher at forest edge than at forest core, both for all understorey plants and for forest specialist species.…”
Section: Discussionmentioning
confidence: 51%